Causal Relationships of Circulating Inflammatory Proteins and Portal Vein Thrombosis: A Mendelian Randomization Study - Zhang, Bihui; Yao, Ziping; Li, Pengyu; Niu, Guochen; Yan, Ziguang; She, Kang; Cheng, Gong; Yang, Min (Seminars in Thrombosis and Hemostasis, 2024)
Portal vein thrombosis (PVT) is commonly encountered in patients with cirrhosis, challenging our understanding of its development, particularly the ambiguous contribution of inflammation. This study utilized Mendelian randomization (MR) to explore the causal impact of circulating inflammatory markers on PVT.Employing a two-sample MR framework, we merged genome-wide association study (GWAS) meta-analysis findings of 91 inflammation-associated proteins with independent PVT data from the FinnGen consortium's R10 release. A replication analysis was performed using a distinct GWAS dataset from the UK Biobank. Inverse variance weighting, MR-Egger regression, weighted median estimator, and Mendelian Randomization Pleiotropy RESidual Sum and Outlier were used for analysis, supplemented by multivariable MR (MVMR) to adjust for cirrhosis effects.Findings indicate a significant inverse association between the genetically inferred concentration of eukaryotic translation initiation factor 4E-binding protein 1 (4E-BP1) and PVT risk, evidenced by an odds ratio (OR) of 0.37 (95% confidence interval [CI]: 0.21–0.67; p = 9.2 × 10−4; adjusted for multiple testing p = 0.084). This association was corroborated in the replication phase (OR = 0.39, 95% CI: 0.17–0.93; p = 0.03) and through MVMR analysis (OR = 0.34, 95% CI: 0.15–0.79; p = 0.012). Sensitivity analyses disclosed no evidence of heterogeneity or pleiotropy.Our investigation emphasizes the 4E-BP1 as a protective factor against PVT, underscoring its potential relevance in understanding PVT pathogenesis and its implications for diagnosis and therapy.
Keywords: portal vein thrombosis; Mendelian randomization; inflammatory proteins; biomarker; FinnGen